Effect of folic acid and tetrahydrofolate on tissue arsenic level in rat (Bangladesh Journal of Pharmacology, 2010)
Quest is still going on for a cheap, effective, and easily available remedy for chronic arsenic toxicity. This study was designed to investigate the effects of folic acid and tetrahydrofolate in lowering the arsenic burden in tissues. Rats received arsenic at 700 µg/day by gavage for 28 days except the control group. Arsenic accumulation was significantly lowered (p